A nomogram for predicting survival and retroperitoneal lymph node dissection treatment in patients with resected testicular germ cell tumors. Issue 3 (29th May 2019) - Wu, Yougen; Meyers, Jeffrey P.; Shi, Guowei; Jin, Zhi; Xia, Ju; Gu, Yuting; Qian, Qingqing; Hong, Yang
Abstract: Background and Objectives: To build nomogram incorporating potential prognostic factors for predicting survival outcomes of testicular germ cell tumors (TGCT) patients after resection of the primary tumor. Methods: Data of TGCT patients from the Surveillance, Epidemiology, and End Results database (2010‐2016) who underwent resection of the primary tumor were collected. Overall survival (OS) and cancer‐specific survival (CSS) were analyzed by using Cox regression models, nomogram, Kaplan‐Meier method, and log‐rank test. Results: We identified 7272 TGCT patients. Age at diagnosis, histology, tumor size, American Joint Committee on Cancer (AJCC) staging system, and number of metastases sites were independent prognostic factors and were integrated into nomograms. The nomograms had higher C‐indexes for both OS and CSS compared with the AJCC 7th staging system (0.881 vs 0.831 and 0.895 vs 0.856, respectively). Moreover, the new stratification of risk groups based on the nomograms showed a more significant distinction between Kaplan‐Meier curves for survival outcomes than the AJCC staging system. Retroperitoneal lymph node dissection was associated with statistically improved survival probability in the nomogram middle‐risk group in resected TGCT patients. Conclusion: The novel nomogram‐based staging system could provide satisfactory risk stratification and survival prediction ability beyond traditional AJCC staging systems.